Perencaaan Penggunaan Lahan Dan Pengaruhnya Terhadap Sumberdaya Air Di DAS Way Besai-Lampung - Ashadi Maryanto; Kukuh Murtilaksano; Latief Mahir Rachman (Jurnal Penelitian Kehutanan Wallacea, 2014)
The problems on water resource are the decreasing of water supply due to the impact of land use changes. The population growth and the rising economy activity lead to the increasing of water demands. Way Besai area of 44,720 hectares has an important role in the provision of water resources. The aims of this research are: to assess the water supply and demand, to assess the water balance and, to formulate the best recommendation of land management planning. This research was conducted in 2011. The SCS (Soil Conservation Service) model was applied to determine land use planning scenarios and run-off prediction. The result shows that the water demand in Way Besai Watershed is 441,450,909m3/year, while water supply is 460,452,600 m3/year. Application of community forestry by applying agroforestry system, implementation of forest rehabilitation on area outside HKm permit, and conducting the change for coffee monoculture to mixed coffee crop in the area outside the forest is considered the best scenario of land management for Way Besai watershed. This scenario could produce 1,055.79 mm/years run-off, coefficient total runoff is 38.52%, water supply is 472,147,141 m3/years, storage is 7,911,616 m3/years and, can meet the of water demand in the dry months at 58.48%.